Primary Squamous Cell Carcinoma of Thyroid: A Rare Entity - Rahulkumar N. Chavan; Bhargav Chikkala; Cinjini Biswas; Somak Biswas; Diptendra Kumar Sarkar (Case Reports in Pathology)
Primary squamous cell carcinoma (PSCC) of thyroid is an extremely rare malignancy of thyroid. Herewith, we describe a case report of female patient who presented with neck swelling; FNAC misdiagnosed it as papillary carcinoma of thyroid but, after resection, biopsy revealed it to be a case of squamous cell carcinoma of thyroid. After extensive investigations no possible primary focus of squamous cell carcinoma was found elsewhere, so diagnosis of primary squamous cell carcinoma of thyroid was made. Patient underwent chemoradiation but still patient succumbed to death within a year.